(untitled) - Lithgow, John; 1945-; Payne, C. F. (New York, 2002)
Micawber, a squirrel fascinated by art, leaves a museum with an art student and secretly uses her supplies to make his own paintings.
Keywords: Museums; Artists; Fiction; Fiction; Squirrels; Fiction; Stories in rhyme